A research about the level of customer satisfaction towards Putra Specialist Hospital (Batu Pahat) Sdn. Bhd. / Siti Zanita Raujan - Raujan, Siti Zanita (2010)
The objectives of this research are to analyze the level of customer satisfaction towards Putra Specialist Hospital (Batu Pahat) Sdn. Bhd, to identify a significant relationship between complaint management and satisfaction and to justify significant relationship between quality of services and customer satisfaction. The research methodology used in this research are questionnaires, observations, and simple random sampling. The results of the research were obtained by reliability test, frequency distribution and pearson correlation analysis. The process of analyzing and interpreting the data were presented through tables and graphs. Base on the findings, all objectives were achieved because the dependent variable and all independent variables are reliable and all independent variables have significant relationship with the dependent variable.